2016
DOI: 10.1128/aac.02017-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Residues W228 and Y233 in the Structure and Activity of Metallo-β-Lactamase GIM-1

Abstract: e Metallo-␤-lactamases (MBLs) hydrolyze virtually all ␤-lactam antibiotics, including penicillins, cephalosporins, and carbapenems. The worldwide emergence of antibiotic-resistant bacteria harboring MBLs poses an increasing clinical threat. The MBL German imipenemase-1 (GIM-1) possesses an active site that is narrower and more hydrophobic than the active sites of other MBLs. The GIM-1 active-site groove is shaped by the presence of the aromatic side chains of tryptophan at residue 228 and tyrosine at residue 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The class B MBLs can be divided into four subclasses according to their structure: (a) B1aVIM, imipenemase (IMP), DIM, SPM; (b) B1b: NDM, (c) B2: cphA, (d) B3: LI and AIM [37,60]. Moreover, Tripoli metallo-β-lactamase (TBM-1) was also included in MBLs [58,61].…”
Section: Factors and Mechanisms Involved In Resistance To β-Lactam Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The class B MBLs can be divided into four subclasses according to their structure: (a) B1aVIM, imipenemase (IMP), DIM, SPM; (b) B1b: NDM, (c) B2: cphA, (d) B3: LI and AIM [37,60]. Moreover, Tripoli metallo-β-lactamase (TBM-1) was also included in MBLs [58,61].…”
Section: Factors and Mechanisms Involved In Resistance To β-Lactam Anmentioning
confidence: 99%
“…For instance, GIM-1 MBL was reported in a clinical isolate (P. aeruginosa) in Germany in year 2002, irstly. In recent years, GIM-1 was started to be reported in other bacterial species such as S. marcescens, E. cloacae and Acinetobacter pitii [60,67]. Similarly, SIM-1 was obtained uncommonly and an integron-encoded blaSIM-1 was reported from Acinetobacter baumannii in Korea irstly [68].…”
Section: Factors and Mechanisms Involved In Resistance To β-Lactam Anmentioning
confidence: 99%
“…Previous studies found that substitutions of residue 228 affected catalytic efficiency in, e.g., GIM-1 (25). Residue 228 has been thoroughly studied in several MBL enzymes; however, a proline variant similar to that found in TMB-2 has been described only in a VIM-2 R228P mutant (11).…”
mentioning
confidence: 99%
“…Residue 228 has been thoroughly studied in several MBL enzymes; however, a proline variant similar to that found in TMB-2 has been described only in a VIM-2 R228P mutant (11). Residue 228 is located in MBL loop L3 (residues 223 to 240) and has been reported to contribute to substrate specificity (25,26) and to be involved in inhibitor binding (8,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation